1980
DOI: 10.1071/wr9800001
|View full text |Cite
|
Sign up to set email alerts
|

Does dingo predation control the densities of kangaroos and emus?

Abstract: The density of red kangaroos in the sheep country of the north-west corner of New South Wales is much higher now that it was last century. It is also much higher than the present density across the dingo fence in the adjacent cattle country of South Australia and Queensland. The picture is similar for emus. Farther east, about halfway along the New South Wales–Queensland border, no difference in density between the two States could be detected for red kangaroos, grey kangaroos or emus. We examine and discard s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
93
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(111 citation statements)
references
References 6 publications
18
93
0
Order By: Relevance
“…Such a comparison should provide some insight into whether dingoes are in fact regulating kangaroo and emu populations outside the dingo fence. These data provide an obvious extension to those of Caughley et al (1980), who reported the densities of kangaroo and emu populations in winter 1976 on both sides of the dingo fence in South Australia, New South Wales and Queensland.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…Such a comparison should provide some insight into whether dingoes are in fact regulating kangaroo and emu populations outside the dingo fence. These data provide an obvious extension to those of Caughley et al (1980), who reported the densities of kangaroo and emu populations in winter 1976 on both sides of the dingo fence in South Australia, New South Wales and Queensland.…”
Section: Introductionsupporting
confidence: 75%
“…Densities were log e -transformed to stabilise variances. Caughley et al (1980) suggested that the change in kangaroo density with increasing distance from the dingo fence would reflect the impact that dingoes are having on the population. This trend in density will form a step at the fence if that fence is an effective barrier to dingoes and if dingoes strongly limit kangaroo populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixed relationships between dingoes and macropods have been found in temperate areas over longer timeframes (Claridge et al 2010;Arthur et al 2013). These studies support observations described here and elsewhere which report that dingoes can limit kangaroo populations in open areas under certain conditions (Choquenot and Forsyth 2013;Allen et al 2014a;Prowse et al 2014), and that the greatest densities of kangaroos occur in places relatively devoid of dingoes (Caughley et al 1980;Pople et al 2000;Letnic and Crowther 2013. Annual kangaroo abundance estimates for the NE region would have been immeasurably useful to our study, though none are available because cattle producers there have not considered kangaroo abundances great enough to warrant establishment of a harvesting industry -the ultimate purpose behind kangaroo density surveys (DEH 2008). However, anecdotal reports claim that 'most of the kangaroos in NSA are in the NW because they bait dingoes there', concurring with several geographically-limited studies (Caughley et al 1980;Pople et al 2000;Newsome et al 2001;Fillios et al 2010;Letnic and Crowther 2013;Allen et al 2014a) that report kangaroo abundances to be persistently low in the NE region.…”
Section: Accepted M Manuscriptsupporting
confidence: 90%
“…However, periods of spatiotemporally intensive control efforts can temporarily suppress dingo population abundances (Fleming et al 2001;Allen et al 2013a). Importantly, dingoes are also thought to suppress kangaroos (Caughley et al 1980;Pople et al 2000;Fillios et al 2010;Letnic and Crowther 2013), one of dingoes' primary prey in arid areas (Corbett and Newsome 1987;Thomson 1992;Allen and Leung 2012). Intensive dingo control is expected to free kangaroos from dingo suppression either by reducing dingo abundance or altering their social structure or group hunting abilities in ways that alleviate kangaroo predation (Allen 2013;Choquenot and Forsyth 2013;Prowse et al 2014).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%